Assessment of genetic variability, correlation and path analysis in sesame (Sesamum indicum L.): ASSESSMENT OF GENETIC VARIABILITY, CORRELATION AND PATH ANALYSIS IN SESAME - CHEGURI PRATYUSHA,; SIMA SINHA,; SATYENDRA,; DHARAMSHEELA THAKUR,; S N SINGH, (Journal of Oilseeds Research, 2022)
The present study was attempted with thirty-eight genotypes including three checks(GT-10, TKG-22, JTS-08). The experiment was carried out in randomized block design in three replications to evaluate variability, association between various economic traits, direct and indirect effect of different characters on yield. The observations were recorded for days to 50 percent flowering, productive branches, plant height (cm), height of 1st capsule bearing node (cm), number of capsules per plant, number of seeds per capsule, capsule length(cm), inter node length (cm), days to maturity, 1000-grain weight (g), percentage of oil and yield (g/plant). Analysis of variance revealed significant differences among the genotypes for all the characters. The magnitude of phenotypic coefficient of variance (PCV) and genotypic coefficient of variance (GCV) was larger for yield, number of productive branches, height of first capsule bearing node and number of capsule/plant and inter-node length. Genetic advance as per cent of mean for yield, number of productive branches, height of first capsule bearing node, number of capsules per plant and internode length were higher in sesame genotype. Correlation coefficient exhibited significant and high positive correlation for number of productive branches, number of capsules per plant and number of seeds per capsule and maturity. Path analysis indicated that the trait number of seeds per capsule, number of productive branches and number of capsules per plant had high direct positive effect on grain yield. These traits to be given due importance in the sesame improvement programme.